Periapical bone healing following endodontic treatment on the right lower premolar - Lydia Tadjudin; Juanita Gunawan; Dina Ratnasari (Wolters Kluwer Medknow Publications, 2019)
Background: Acute exacerbation represents a painful condition whereby the tooth becomes highly sensitive to percussion and bite testing, and it can be aggravated by traumatic occlusion. In general, it results from earlier acute apical periodontitis. Bone destruction can be detected via a radiographic examination, and it can be seen as a radiolucent area at the periapex. Bone resorption is caused by osteoclast activation, which results from pulp inflammation. Nonsurgical endodontic treatment is typically performed to resolve the condition. This study aimed to provide an overview of both the treatment protocol and the role of 2% chlorhexidine gluconate as an endodontic irrigant. Case Report: A 38-year-old woman presented with a major complaint regarding tenderness in her lower second right premolar. The patient reported having experienced similar pain approximately 8 months previously. Clinically, the tooth had lost 50% of its coronal structure, which indicated a Class II cavity. Radiographically, bone resorption was detected in the periapical area of the tooth. An analgesic had been consumed for approximately 3 days. The cavity was cleaned and opened, and working length measurements were performed using an electronic apex locator and conventional radiography. Biomechanical preparation was done using ProTaper NEXTTM files, until size X3. Irrigation was performed using 5.25% sodium hypochlorite at each file change and continued with 17% ethylenediaminetetraacetic acid and 2% chlorhexidine for final irrigation. Sterile Aqua Dest was used for each irrigation change to avoid interaction between irrigants. Obturation was performed by means of warm vertical compaction with an epoxy resin-based sealer. An endocrown composite was recommended for permanent restoration. Four months of follow-up revealed bone regeneration and healing. Conclusion: Bone resorption is a common finding in a diseased tooth, and it stems from the persistent inflammatory process. Osteoclasts are responsible for both bone demineralization and activated pro-inflammatory cytokines. The correct endodontic treatment protocol plays an essential role in periapical bone healing.